Firearm ownership in veterans entering residential PTSD treatment: Associations with suicide ideation, attempts, and combat exposure. Issue 1 (30th September 2015) - Smith, Phillip N.; Currier, Joseph; Drescher, Kent
Abstract: This study aimed to describe the frequency of firearm ownership in veterans entering residential treatment for posttraumatic stress disorder (PTSD) and examine the association of firearm ownership with suicide ideation and suicide attempt history, combat exposure, and PTSD symptom severity. Two samples of veterans entering residential PTSD treatment were assessed at intake using self-report measures. Approximately one third of participants endorsed firearm ownership across the two samples. Analyses with a sample predominantly comprised of Vietnam Veterans found that those who endorsed both suicide ideation and prior suicide attempts were less likely to own a firearm compared to suicide ideators and non-suicidal participants. In addition, more frequent combat exposure, but not PTSD symptom severity, was associated with firearm ownership in both samples and most participants endorsed using safe storage practices. These lower rates of firearm ownership generally, and in those with suicide ideation and prior attempts in particular, may reflect an increased focused on means restriction in treatment for combat-related PTSD. Means restriction counseling among PTSD treatment seeking veterans should target those with combat exposure. Highlights: Rates of firearm ownership and relations among suicide risk factors were examined. Two samples of veterans entering residential treatment for PTSD were studied. One third of all participants endorsed firearm ownership. Suicide ideators with prior suicide attempts were least likely to own a firearm. More frequent combat exposure was associated with firearm ownership.